Degree of Acidity, Salivary Flow Rate and Caries Index in Electronic Cigarette Users in Sleman Regency, Indonesia - Dyah Ayu Lestari; Regina TC. Tandelilin; Friska Ani Rahman (Indonesian Dental Association, 2020)
Introduction: The Yogyakarta Special Region ranks sixth for highest number of smokers of the 33 provinces in Indonesia. Smokers account for 31.6% of the total population. Sleman Regency ranks fourth in daily consumption of cigarettes of the five regencies or cities in Yogyakarta. The body part most exposed to direct cigarette smoke is the oral cavity. Saliva is a liquid secreted inside the oral cavity to act as a buffer. Nicotine content in conventional cigarettes is known to diminish the salivary flow rate and the acidity (pH) of the saliva. A continual decrease in saliva pH over time may cause dental caries. The use of electronic cigarettes is a nicotine replacement therapy (NRT) method to help people quit smoking; they emit a lower nicotine level than conventional cigarettes. Objective: The aim of this study was to evaluate the saliva pH, salivary flow rates, and caries index of electronic cigarette smokers. Methods: This study used a cross-sectional method to compare the saliva pH, salivary flow rate, and caries index of 30 smokers of electronic cigarettes and 30 non-smokers as a control group. Data were analyzed using SPSS version 22.0 software and considered statistically significant at p < 0.05. Results: The Mann-Whitney analysis showed a significant difference in the saliva pH between electronic cigarette smokers and non-smokers. Independent T-Test analysis showed no significant difference in the salivary flow rates of the two groups. The Mann-Whitney analysis also showed no significant difference in the caries index of the groups. Conclusion: Results indicated that there is a significant difference in the saliva pH of electronic cigarette smokers, while the salivary flow rates and caries indices of electronic cigarette smokers and non-smokers were similar.